2022
DOI: 10.1007/s10959-021-01153-x
|View full text |Cite
|
Sign up to set email alerts
|

Amalgamated Free Lévy Processes as Limits of Sample Covariance Matrices

Abstract: We prove the existence of joint limiting spectral distributions for families of random sample covariance matrices modeled on fluctuations of discretized Lévy processes. These models were first considered in applications of random matrix theory to financial data, where datasets exhibit both strong multicollinearity and non-normality. When the underlying Lévy process is non-Gaussian, we show that the limiting spectral distributions are distinct from Marčenko–Pastur. In the context of operator-valued free probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…See, p.766 (Characterization 1) in (Bose et al, 2002). Sample Lévy Covariance ensemble in (Zitelli, 2022) serves as a specific example of such matrices.…”
Section: Heavy-tailed Entries Suppose {Xmentioning
confidence: 99%
See 2 more Smart Citations
“…See, p.766 (Characterization 1) in (Bose et al, 2002). Sample Lévy Covariance ensemble in (Zitelli, 2022) serves as a specific example of such matrices.…”
Section: Heavy-tailed Entries Suppose {Xmentioning
confidence: 99%
“…They found that a class of partitions, the special symmetric partitions, play a crucial role in the moments of the LSD. Matrices whose entries satisfy conditions like (1.1), are referred to as matrices with exploding moments and have been considered by several authors ((Benaych-Georges and Cabanal-Duvillard, 2012), (Male, 2017), (Noiry, 2018), (Zitelli, 2022)). In particular, the S matrix with exploding moments have been studied in Theorem 3.2 of (Benaych-Georges and Cabanal-Duvillard, 2012), Proposition 3.1 of (Noiry, 2018), and Theorem 1 of (Zitelli, 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation